PENERAPAN MODEL PEMBELAJARAN DISCOVERI LEARNING PADA MATERI TEKS ANEKDOT KELAS X SMK N JATIROGO - Faizah, Nurul; Mustofa, Mustofa (MEDIA DIDAKTIKA, 2024)
Learning that discovers concepts through a series of data or information obtained through observation or experimentation. Discovery lerning is used to develop concepts under teacher supervision where learning is cognitive learning that requires teachers to be more creative in creating situations that can make students learn actively find their own knowledge. Vocational education unit is chosen to be the object of research because students get Indonesian language subjects basic competence in understanding anecdotal texts. The strategy used by teachers to improve the effectiveness and active learning of students is by utilizing the Discovery Learning learning model.